2-carba-cyclic phosphatidic acid modulates astrocyte-to-microglia communication and influences microglial polarization towards an anti-inflammatory phenotype. (16th February 2023) - Takei, Rino; Nakashima, Mari; Gotoh, Mari; Endo, Misaki; Hashimoto, Kei; Miyamoto, Yasunori; Murakami-Murofushi, Kimiko
Graphical abstract: Highlight: Astrocyte conditioned media (2ccPA-ACM) was collected from 2ccPA-treated astrocytes. 2ccPA-ACM decreased the ratio of M1 phenotype microglia. 2ccPA-ACM increased the ratio of M2 phenotype microglia. 2ccPA-ACM suppressed the expression of pro-inflammatory cytokines in microglia. Abstract: 2-carba-cyclic phosphatidic acid (2ccPA) suppresses microglial and astrocyte inflammation for neuronal survival following traumatic brain injury. However, it remains unknown how 2ccPA regulates microglial activation. In this study, to elucidate the 2ccPA behavior in glial communication, we collected the astrocyte conditioned media (ACM) from primary astrocyte cultures that were treated by lipopolysaccharide (LPS) and 2ccPA and analyzed the alteration of microglial inflammation caused by the ACM treatment. The addition of the ACM derived from LPS- and 2ccPA-double treated astrocytes to microglia decreased the CD86 + pro-inflammatory M1 microglia, which were upregulated with the ACM collected from astrocytes treated by LPS without 2ccPA, while the direct addition of LPS and 2ccPA to microglia failed to decrease the CD86 + microglia to the basal level. We confirmed that the ACM from LPS- and 2ccPA-treated astrocytes increased the ratio of CD206 + anti-inflammatory M2 microglia to total microglia, whereas direct treatment of microglia with LPS and 2ccPA had no effect on the CD206 + microglia ratio, demonstrating the importance of astrocyte intervention in microglial polarization. In addition, we examined whether astrocytes modulate the 2ccPA-regulated proinflammatory cytokine production derived from microglia. The addition of the ACM from LPS- and 2ccPA-treated astrocytes to microglia remarkably canceled the LPS-induced upregulation of IL-1β, IL-6, and TNF-α secreted from microglia, while the direct addition of LPS and 2ccPA to microglia showed no affect. Therefore, our results indicate that astrocytes mediate the 2ccPA function to shift microglia towards the M2 phenotype by interfering with the polarization of M1 microglia and to suppress cytokine production.